Molecular Characterization of a Novel Shell Matrix Protein With PDZ Domain From Mytilus coruscus - Sun, Qi; Jiang, Yuting; Yan, Xiaojun; Fan, Meihua; Zhang, Xiaolin; Xu, Huanzhi; Liao, Zhi (Frontiers in Physiology, 2020)
Mollusk shells are products of biomineralization with excellent mechanical properties and the shell matrix proteins (SMPs) have important functions in the shell formation. A novel SMP with PDZ domain (PDZ-domain-containing-protein-1, PDCP-1) was identified from the shell matrices of Mytilus coruscus. In this study, the gene expression, function, and the location of PDCP-1 were analyzed. The PDCP-1 was characterized as a 70 kDa protein with a PDZ (postsynaptic density/discs large/ zonula occludes) domain and a ZM (ZASP-like motif) domain. The PDCP-1 gene has high expression level and specific location in the foot, mantle and adductor muscle. Recombinant expressed PDCP-1 (rPDCP-1) showed abilities on the morphological changes of calcite crystals, polymorph change of calcite crystal, binding with both calcite and aragonite crystal, and inhibition of crystallization rate of calcite crystal. In addition, anti-rPDCP-1 antibody was prepared and immunohistochemistry and immunofluorescence analyses revealed the specific location of PDCP-1 in the mantle, the adductor muscle, and the aragonite (nacre and myostracum) layer of shell, suggesting multi-functions of PDCP-1 in biomineralization, muscle-shell attachment, and muscle attraction. Furthermore, pull-down analysis revealed 19 protein partners of PDCP-1 from the shell matrices and provide accordingly a possible interaction network of PDCP-1 in the shell. These results expand the understanding of the functions of PDZ-domain-containing protein in biomineralization and the supramolecular chemistry that contributing to the shell formation.